2021
DOI: 10.2147/dmso.s295960
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of General or Central Obesity and Hypertension on Diabetes: Sex-Specific Differences in a Rural Population in Northeast China

Abstract: Purpose Some studies have established an association between hypertension or obesity and the risk of diabetes. This study aimed to examine the interaction of hypertension and obesity on diabetes. Participants and Methods The data of 11,731 Chinese men and women were analyzed from the 2012–2013 Northeast China Rural Cardiovascular Health Study. The interaction was examined by both additive and multiplicative scales. General obesity was measured by body mass index (BMI); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…We found high prevalence of NHEW and HTEW in females as compared to males, which is more likely to develop T2DM. This result is in line with previous reports in the literature [ 26 , 27 ]. These gender differences may be partly related to sex hormones, such as estrogen.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found high prevalence of NHEW and HTEW in females as compared to males, which is more likely to develop T2DM. This result is in line with previous reports in the literature [ 26 , 27 ]. These gender differences may be partly related to sex hormones, such as estrogen.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were consistent with a previous study conducted in northeast China, which observed the interactive association of hypertension and WHtR with T2DM. The authors of that study found that the risk for T2DM is 3.1-, 2.4-, and 4.9-fold higher in individuals with an elevated WHtR, hypertension, and both conditions, respectively, than in individuals without these conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When interaction among aetiologic factors exists in a target population, adequately accounting for that interaction by researchers allows a more accurate description of the risk factors’ potential to cause harm, and hence the public health measures that are necessary to reduce that harm 42. Interaction can be assessed on both additive and multiplicative scales,43 44 whereas multiplicative interaction may be viewed as relevant to etiologic understanding, additive interaction may be viewed as a public health measure relevant to prioritising resource allocation in efforts at prevention. Consequently, both additive and multiplicative interaction analysis were performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, Hammer et al reported a correlation of CAD with BMI and WC in women [ 45 ]. Another study in Chinese females reported that a high BMI in addition to hypertension accelerated the risk for type II diabetes mellitus [ 46 ], an additional risk for cardiovascular events. Similarly, Chen et al studied Chinese people with normal BMIs for their predisposition to develop type II diabetes mellitus depending on their WC.…”
Section: Discussionmentioning
confidence: 99%